P–315 Ultrasound diagnosis of adenomyosis: impact on pregnancy rate in ivf cycles with donated oocytes. (6th August 2021) - Exacoustos, C; Loiudice, L; Cosentino, M; Galliano, D; Martire, F G; Pellicer, A
Abstract: Study question: The aim was to evaluate in patients who underwent embryo transfer (ET) in an oocyte donation cycle, the impact of adenomyosis, diagnosed by transvaginal sonographic (TVS), on the implantation rate. Summary answer: We observed a slightly higher miscarriage rate in the first trimester in patients with adenomyosis in particular in the diffuse type. What is known already: What we know from literature is that there are pro studies such as Costello and Vercellini's which show a reduced pregnancy rate and birth rate, and cons studies which find no effects at all of adenomyosis on IVF treatments. However, both show an increased risk of miscarriage and obstetric complications Study design, size, duration: This prospective observational study involved a total of 72 patients: 33 with adenomyosis and 39 without adenomyosis from June 2019 to December 2020. All had a workup which included history, pelvic exam and 2/3D TVS scan which was saved as images, videoclips and volumes and stored. The off line evaluation was performed blind to IVF indication and outcomes by expert sonographer, who assessed the presence or absence of TVS signs of adenomyosis. Participants/materials, setting, methods: All the patients aged ≤ 45 years old undergoing, for several personal problems, their first oocyte donation at IVI center Rome.Patients were divided into 2 groups according to findings on a baseline pre-treatment TVS: patients with and without adenomyosis. In the patients with adenomyosis, the disease was further classified according to type (diffuse, focal), localization (inner and outer myometrium) and extension inside the uterus (mild, moderate, severe) and correlated to pregnancy rate and outcome Main results and the role of chance: A total of 72 patients were included in this study: 33 with adenomyosis and 39 without adenomyosis. The presence, type and degree of adenomyosis doesn't show a correlation to embryo implantation rate (64.1% in the control group vs 63.6% in adenomyosis group). However we found an increased risk of early miscarriage in the patients with adenomyosis ( 12% in the control group vs 23.8% in adenomyosis group). Women with adenomyosis that infiltrated only the external myometrium showed a lower pregnancy rate (40%) compared to those who had the involvement of only the inner myometrium (77, 7%). The presence of ultrasound findings of focal disease was associated with a lower pregnancy rate (53, 3%) compared to the diffuse disease (72, 2%); We observed a slightly higher miscarriage rate in the first trimester in patients with adenomyosis in particular in the diffuse type .The presence, type and degree of adenomyosis doesn't show a correlation to embryo implantation rate. Limitations, reasons for caution: Most of the patients included in our study has an age > 40. This could determine an increased number of high-risk pregnancies. Wider implications of the findings: Results of this study may be used to evaluate the impact of different medical or surgical treatment in women with adenomyosis undergoing IVF. Trial registration number: Not applicable